MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SEKOLAH DASAR (STUDI EKSPERIMEN KUASI SISWA KELAS V SD NEGERI 179 PEKANBARU) - Gunawan, Indra Gunawan Indra; Alpusari, Mahmud Alpusari Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: One of factor that influence low students achievement that was students hard to understand in science subject. Students didnt understand the concept of the subject. Thats why the author need to did the research by Problem Based Learning (PBL). This model be able to make student built their own knowledge, increase activity, increase the independent, systematic thinking, logic and accurate for acquire ability to solve the problem in a rational manner. The main purpose of this research was for identify increase students achievement science between student who got Problem Based Learning (PBL) and student who got conventional learning. The research method used a quasi-experimental which divide 2 classes, experiment class and control class. This research was done in SDN 179 Pekanbaru between class Vb students as a control and class Vc students as a experiment. Data research was analyzed by Wilcoxon Signed Rank Test with degree of freedom Î± = 0,05. The result of analysis data, in experiment class got average pretest 42,2 became 50,2 in a average posttest. and in the control class got average pretest 39,1 became 46,13 for average posttest. The result of this research showed that there was different average from both of classes but based on statistic there was no significant difference toward increase students achievement science between students who got Problem Based Learning (PBL) and students who got conventional learning.Key Word: Problem Based Learning, Studentâs Achievement.